Building Students’ Social Caring Character through Service-Learning Program / Penanaman Karakter Kepedulian Sosial Anak Melalui Pembelajaran Service Learning - Moch Sya'roni Hasan; Mufidah Ch; Moh Padil (Al-Mudarris: Journal Of Education, 2021)
To support children in understanding and having social caring attitudes, the character should be imparted earlier. Children were required to be trained and familiarized by regularly being exposed with real situations and conditions. Therefore, an approach combining the learning process with community service activities as an effort to shape the students’ social caring personality was needed; one of them was through service-learning programs. This study was aimed to describe the process of building the students’ social caring principles through implementing service-learning programs in Al Urwatul Wutsqo Jombang and Darussalam Kediri Islamic boarding schools. This research was a qualitative study with a multisite study design. The data was collected using in-depth interview techniques, participatory observation, and documentation. Furthermore, the data was analyzed through some stages, covering data collection, condensation, and presentation, drawing a conclusion, and validating the findings by extending participation, using triangulation techniques of sources, theories, and methods as well as conducting persistent observations. The research informants were pesantren caretakers, teachers, students, and society. The result showed that the implementation of building students’ social caring character through service learning model was carried out in three stages, namely habituation, evaluation (muhasabah), and modeling.